Work Fulfillment in Hybrid Work Systems: The Role of Work–Life Balance, Flexible Work Arrangements, and Employee Engagement - Silvi Aurelia Nur Pratama; Titik Rosnani; Nurul Komari; Yulyanti Fahruna (Al-Qalam Institue, 2026)
This study aims to examine the influence of work–life balance and flexible work arrangements on work fulfillment among Generation Z employees in hybrid work systems, with employee engagement acting as a mediating variable. A quantitative research design was employed by collecting data from 200 Generation Z employees who had at least one year of experience working in a hybrid system. Data were gathered through an online questionnaire using validated measurement scales and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results reveal that work–life balance and flexible work arrangements have a positive and significant effect on employee Engagement and work fulfillment. Employee engagement also significantly influences work fulfillment and partially mediates the relationships between work–life balance, flexible work arrangements, and work fulfillment. The model shows moderate explanatory power with R² values of 0.315 for employee engagement and 0.371 for work fulfillment. These findings imply that organizations should design hybrid work policies that emphasize balanced work-life boundaries, structured flexibility, and engagement-enhancing practices to improve sustainable work fulfillment among Generation Z employees.